Search for the Standard Model Higgs boson produced by vector-boson fusion and decaying to bottom quarks in root s=8TeV pp collisions with the ATLAS detector - Çetin, Serkant Ali (Springer, 2016)
A search with the ATLAS detector is presented for the Standard Model Higgs boson produced by vector-boson fusion and decaying to a pair of bottom quarks, using 20.2 fb(-1) of LHC proton-proton collision data at root s - 8 TeV. The signal is searched for as a resonance in the invariant mass distribution of a pair of jets containing b-hadrons in vector-boson-fusion candidate events. The yield is measured to be -0.8 +/- 2.3 times the Standard Model cross-section for a Higgs boson mass of 125 GeV. The upper limit on the cross-section times the branching ratio is found to be 4.4 times the Standard Model cross-section at the 95% confidence level, consistent with the expected limit value of 5.4 (5.7) in the background-only (Standard Model production) hypothesis.
Keywords: Hadron-Hadron scattering (experiments); Higgs physics; proton-proton scattering